Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1177/02654075030201004
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Styles of Self-Focused Autonomy, Other-Focused Connectedness, and Mutuality across Multiple Relationship Contexts

Abstract: This study examined relationship styles of self-focused autonomy, other-focused connectedness, or mutuality with mothers, fathers, best friends, and romantic partners to determine if styles would be used consistently or would vary across relationships. Participants included 257 college students (M = 21.6 years). Mutuality was the most commonly reported relationship style in all relationship contexts, and no sex differences in style were found. Most participants reported using more than one relationship style a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 26 publications
4
11
2
1
Order By: Relevance
“…Our results also indicated that the emotional autonomy of young college students correlates negatively with perceived family social support, with those with greater emotional autonomy having less confidence in the support they feel they receive from their parents. These results are consistent with the findings of previous studies by Neff and Harter () and Yu (), who found an association between high levels of emotional autonomy and weaker, less cohesive family structures.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results also indicated that the emotional autonomy of young college students correlates negatively with perceived family social support, with those with greater emotional autonomy having less confidence in the support they feel they receive from their parents. These results are consistent with the findings of previous studies by Neff and Harter () and Yu (), who found an association between high levels of emotional autonomy and weaker, less cohesive family structures.…”
Section: Discussionsupporting
confidence: 93%
“…However, other authors dispute the argument that achieving emotional autonomy is a developmental task, supporting instead the theory that adolescents who feel more emotionally autonomous from their parents perceive lower quality, less affection and less love in their relationships with them (Ryan & Lynch, ; Zimmer‐Gembeck, Madsen & Hanisch, ). These studies have also shown that high levels of emotional autonomy are associated with challenges in family relationships during adolescence and emerging adulthood, less cohesive family structures marked by a lack of emotional intimacy and communication, and more difficult parent‐child relationships (Neff & Harter, ; Yu, ). Thus, according to this latter perspective, high emotional autonomy is associated, at least during these years, with feelings of insecurity, negative self‐concept, depression and other behaviors linked to internalizing problems (Delhaye, Kempenaers, Linkowski, Stroobants & Goossens, ; Ryan & Lynch, ).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, those with a high level of parental bonding may tend to attune themselves to parental needs, feelings, and opinions, maintaining emotional closeness with their parents. Unlike the majority of previous studies on Western youth, Neff and Harter (2003) showed that college students in the United States who endorsed autonomous behavior reported poorer relationships with their parents than their counterparts; they further suggested that these students may suffer from a lack of emotional closeness to their parents.…”
Section: Discussioncontrasting
confidence: 86%
“…Interestingly, in this normative sample, girls whose rejection sensitivity increased over the adolescent transition were those most likely to adapt a submissive stance toward their partners. Overaccommodation and the tendency focus on others' needs at one's own expense is an indicator of a failure to establish mutuality of autonomy, the capacity to “balance concerns with the self's and other's needs and feelings and to maintain both separate space and closeness in the relationship” (Neff & Harter, , p. 83). Research evidences that young adults who fail to achieve this kind of balance between focusing on the needs of self or other are less psychologically well‐adapted and less satisfied in their intimate relationships than their peers (Neff & Harter, ), and their relationships are more likely to involve the use of abusive strategies for conflict resolution, such as relational aggression (Kerig & Swanson, ; Kerig, Swanson, et al., ).…”
Section: Anticipating Rejectionmentioning
confidence: 99%